Synthesis and In Vitro Antimicrobial and Anthelminthic Evaluation of Naphtholic and Phenolic Azo Dyes - Joseph Kwasi Adu; Cedric Dzidzor Kodjo Amengor; Nurudeen Mohammed Ibrahim; Cynthia Amaning-Danquah; Charles Owusu Ansah; Dorcas Dzifa Gbadago; Joseph Sarpong-Agyapong (Journal of Tropical Medicine)
The antimicrobial activity of 2-naphtholic and phenolic azo compounds was determined against seven microbial species, Staphylococcus aureus (ATCC 25923), Streptococcus pyrogenes (clinical), and Enterococcus faecalis (ATCC 29212), Salmonella typhi (clinical), Pseudomonas aeruginosa (ATCC 27853), Escherichia coli (ATCC 251922), and Candida albicans (ATCC 10231), using the high-throughput spot culture growth inhibition assay (HT-SPOTi). The minimum inhibitory concentrations (MIC) were determined for the active azo dyes. All the azo compounds (A1–B4) were screened for anthelmintic activity against adult Ghanaian earthworms, Hyperiodrilus spp. As part of the systematic investigation for biological activity, all the azo compounds exhibited good antimicrobial activity against the seven human pathogenic microorganisms. All the compounds exhibited anthelminthic activity against adult Ghanaian earthworms, Hyperiodrilus spp.